2016
DOI: 10.1021/acs.inorgchem.6b02430
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the 4-Phenyl-1,2,3-Triazole Moiety as a Versatile Scaffold for the Development of Cytotoxic Ruthenium(II) and Osmium(II) Arene Cyclometalates

Abstract: Herein we report the synthesis, anticancer potency in vitro, biomolecule interaction, and preliminary mode of action studies of a series of cyclometalated 1,2,3-triazole-derived ruthenium(II) (2a-e) and osmium(II) (3a-e) organometallics of the general form [(η-p-cym)RuCl(κ-C^N-L)] with varying substituents in postion 1 of the 1,2,3-triazole moiety. These cyclometalates were characterized by standard analytical methods and their structures unambiguously assigned by single crystal X-ray crystallography. The anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 77 publications
6
29
0
Order By: Relevance
“…Overall, the results of cell cycle modifications revealed that the cellular effects of the Ru-dca complex are much more similar to the effects of cisplatin , while the Os-dca complex showed only a small effect on the cell cycle in the A2780 cells as compared to the negative control. Just for the comparative purposes we may show that similar human cancer cell cycle perturbations were recently reported for half-sandwich complexes [Ru(η 6 - p cym)(L 2 )Cl] and [Os(η 6 - p cym)(L 2 )Cl] containing 1-(4-methoxybenzyl)-4-phenyl-1 H -1,2,3-triazole (HL 2 ) [ 38 ].…”
Section: Resultssupporting
confidence: 58%
“…Overall, the results of cell cycle modifications revealed that the cellular effects of the Ru-dca complex are much more similar to the effects of cisplatin , while the Os-dca complex showed only a small effect on the cell cycle in the A2780 cells as compared to the negative control. Just for the comparative purposes we may show that similar human cancer cell cycle perturbations were recently reported for half-sandwich complexes [Ru(η 6 - p cym)(L 2 )Cl] and [Os(η 6 - p cym)(L 2 )Cl] containing 1-(4-methoxybenzyl)-4-phenyl-1 H -1,2,3-triazole (HL 2 ) [ 38 ].…”
Section: Resultssupporting
confidence: 58%
“… 40 42 Investigations of osmium complexes as alternatives to ruthenium-based anticancer agents have resulted in structurally diverse libraries of osmium complexes with different oxidation states and nuclearity. 43 46 …”
Section: Introductionmentioning
confidence: 99%
“…[145] For several other Rubased compounds, there is some evidence [96,128,138] that they do not influence the immune response itself and might have synergistic effects in combination with cancer immunotherapy. [146] It is certain that RAPTA compounds do not induce the cancer immune response via thioredoxin levels and the regulation of the activity of thioredoxin reductase. [146] It is certain that RAPTA compounds do not induce the cancer immune response via thioredoxin levels and the regulation of the activity of thioredoxin reductase.…”
Section: How To Benefit From and With Immunotherapy?mentioning
confidence: 99%